Socio-Cultural Dynamics of Indian Classical Dance - Archana Ganapathi
Classical Indian dance mirrors traditional Indian culture. Culture diffuses from the lowest levels of simplicity to the strata of complexity. At all rungs of the cultural ladder, gender bias is prominent